EMERGENCY MEDICAL DISPATCHERS' ABILITY TO DETERMINE OBVIOUS OR EXPECTED DEATH OUTCOMES USING A MEDICAL PRIORITY DISPATCH PROTOCOL. Issue 9 (18th August 2016) - Whitaker, Ivan; Olola, Christopher; Toxopeus, Corike; Scott, Greg; Clawson, Jeff; Schultz, Bryon; Robinson, Don; Calabro, Christopher; Gardett, Isabel; Patterson, Brett
Abstract : Abstract previously published in Annals of Emergency Dispatch and Response